Collaboration, critique and a community of peers: the benefits of peer learning groups for screen production research degrees. Issue 1 (2nd January 2016) - Batty, Craig
ABSTRACT: In response to both my own desire for professional development and candidates' desires for more support, in 2012 I began to coordinate a peer-to-peer learning group for creative writing research degree students at RMIT University. Still going strong over three years later, the group brings together creative practice higher degree by research (HDR) candidates working in areas such as prose fiction and nonfiction, screenwriting, poetry and digital narratives. In the context of existing literature on peer-to-peer learning in the HDR space, the group is somewhat unique in that a range of academics from across the host School of Media and Communication supervise the group's members, rather than them all being my own candidates. My role in the group is that of a facilitator, guiding an activity that complements rather than replaces the more traditional supervisor-candidate model of supervision. In this way, the group seeks to re-distribute and enhance the experience of HDR candidates, adding value to their experience of research training through opportunities to collaborate and critique, and through high levels of encouragement from their peers, to present and publish their work, and to work towards a more timely completion. This article draws on the author's experiences of facilitating such a group to discuss the benefits of peer-to-peer learning for creative practice research degrees broadly, and for screen production research degrees specifically. Exploring areas such as collaboration, critique and the building of a community of peers, the article outlines a range of strengths and weaknesses in leading a peer-to-peer learning group at this level. By drawing on the group's activities and reflections from some of its members, the article also seeks to provide guidance to supervisors and candidates working on screen production research degrees who are looking for ways to enhance how they offer and experience research training.